2017
DOI: 10.12957/demetra.2017.25127
|View full text |Cite
|
Sign up to set email alerts
|

Pães De Mel Elaborados Com Farinha De Diferentes Variedades De Banana Verde

Abstract: Pães de mel elaborados com farinha de diferentes variedades de banana verdeHoney Breads made with flour of different varieties of green banana Resumo Objetivou-se desenvolver pães de mel com farinhas de banana verde cozida de duas variedades: prata (FBVCP) e nanicão (FBVCN), caracterizando-os física, química, físico-química e sensorialmente. As polpas de banana verde cozidas foram desidratadas em estufa ventilada a 65ºC/20 h e moídas, obtendo assim as Farinhas de Banana Verde Cozida. Foram desenvolvidas três f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
2
1
2
Order By: Relevance
“…According to Sandrin (2013), oat is a cereal whose structure is different from the others, and in addition to having a high lipid content distributed throughout the entire grain, it is also rich in protein. Unlike the present study, Freitas et al (2017) did not observe significant differences in the lipid and proteins levels in honey breads made with 30% cooked GBF (banana varieties Prata and Grande Naine) partially replacing wheat flour.…”
Section: Physicochemical Characterization and Proximate Composition Of The Cakescontrasting
confidence: 99%
See 1 more Smart Citation
“…According to Sandrin (2013), oat is a cereal whose structure is different from the others, and in addition to having a high lipid content distributed throughout the entire grain, it is also rich in protein. Unlike the present study, Freitas et al (2017) did not observe significant differences in the lipid and proteins levels in honey breads made with 30% cooked GBF (banana varieties Prata and Grande Naine) partially replacing wheat flour.…”
Section: Physicochemical Characterization and Proximate Composition Of The Cakescontrasting
confidence: 99%
“…With the growing and rapid access to information and market trends in the food sector, consumers have increasingly sought healthier products that offer nutritional benefits (Ferronatto, Rossi, & Cappellari, 2020). Food rich in fiber and resistant starch (RS) fall into this group (Freitas, Silveira, Veras, & Santos, 2017), which takes the green banana to a prominent position for being a good source of RS (Reis, Viana, Assis, Sena, Souza, & Amorim, 2019;Campuzano et al, 2018). Additionally, its consumption in the recommended amount directly contributes to the proper functioning of the immune system and intestinal function (Öztürk & Mutlu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Vieira et al (2017) elaborated flour with melon bark also for cupcakes production and obtained a yield of 8.8%, lower only than that found in the flour obtained from the integral shell of dried passion fruit at 70 and 80 °C. Freitas et al (2017) elaborated flours with green bananas of the varieties silver and nanicão for the production of honey loaves and they describe that the final yield of the flour was 17%, higher than those of this research, certainly because the authors used the pulp of the fruit. Santos et al (2015) conducted eight treatments for the flour processing using different parts and maturation stages of the banana banana, being: a) green banana pulp; b) mature banana pulp; c) green banana peel; d) ripe banana peel; e) pulp plus bark of green banana; f) pulp plus ripe banana peel and g) pulp plus green banana peel without sanitizing with sodium hypochlorite and obtained yields of 39.4; 23.81; 8.67; 11.24; 23.34; 25.67 and 23.13% for flour a, b, c, d, e, f and g respectively, it was observed that when using the fruit pulp in the flour preparation the yields were higher.…”
Section: Resultsmentioning
confidence: 59%
“…Por meio do desenvolvimento de três formulações de pão de mel tradicional, com substituição parcial da farinha de trigo pelas farinhas de banana verde cozida de duas variedades prata e nanicão, Freitas et al (2017) avaliaram a aceitabilidade sensorial do produto pela Escala Hedônica de nove pontos, realizada com 73 provadores não treinados, consumidores potenciais do produto. Os resultados do teste de aceitação demonstraram escores médios dos atributos para as três formulações superiores a 7 (gostei moderadamente), situando-se na zona de aceitação pelos provadores, sendo o índice de aceitabilidade maior que 70%.…”
Section: Resultsunclassified